PSYCHOLOGICAL CHARACTERISTICS OF INDONESIAN AND SOUTH KOREAN ATHLETES IN THE ASIAN GAMES - Pulungan, Khoirul Anwar; Suardika, I Kedek; Haryani, Meri; Mile, Rifky; Kadir, Sulasikin Sahdi; Prastyawan, Rifky Riyandi (Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2024)
This research aims to determine: (1) the characteristics of the psychological skills of Indonesian athletes, (2) the characteristics of the psychological skills of South Korean athletes. The type of research used in this research is quantitative descriptive research, using a survey method with a retrospective causal-comparative research design. The population in this study were Indonesian athletes taking part in the 19th Asian Games in 2023 in China, totaling 100 athletes, consisting of 50 Indonesian athletes and 50 South Korean athletes, with an average age of male athletes of 25 years and an average age of female athletes of 20 years. The instrument used in this research is The Psychological Skills Inventory for Sport (PSIS). The data analysis technique uses parametric inferential statistics, with a significance level of 0.05. The results of the research show that: the psychological skill characteristics of South Korean athletes are better with a high average score which has a standard deviation of 19.42, while the psychological skill characteristics of Indonesian athletes are achieved with a medium average score which has a standard deviation of 13.25. The psychological characteristics of South Korean athletes are better than the psychological characteristics of Indonesian athletes. To make it better, it is hoped that further research will be carried out on the psychological characteristics of each sport.Penelitian ini bertujuan untuk mengetahui: (1) karakteristik keterampilan psikologis atlet Indonesia, (2) karakteristik keterampilan psikologis atlet Korea Selatan. Jenis penelitian yang digunakan dalam penelitian ini adalah penelitian deskriptif kuantitatif, menggunakan metode survei dengan desain penelitian a retrospective causal-comparative. Populasi dalam penelitian ini adalah atlet Indonesia yang mengikuti gelaran Asian Games ke-19 tahun 2023 di Cina yang berjumlah 100 atlet, terdiri dari 50 atlet Indonesia dan 50 atlet Korea Selatan, dengan rerata usia atlet putra 25 tahun dan rerata usia atlet putri 20 tahun. Intrumen yang digunakan pada penelitian ini adalah The Psychological Skills Inventory for Sport (PSIS). Teknik analisis data menggunakan statistik inferensial parametrik, dengan taraf signifikansi 0,05. Hasil penelitian menunjukkan bahwa: karakteristik keterampilan psikologis atlet korea Selatan lebih baik dengan capaian nilai rata-rata tinggi yang memiliki standar deviasi 19,42 sedangkan untuk karakteristik keterampilan psikologis atlet Indonesia berada pada capaian nilai rata-rata sedang yang memiliki standar deviasi 13,25. karakteristik psikologi atlet korea selatan lebih baik dari pada karakteristik psikologi atlet indonesia. agar lebih baik, diharapkan selanjutnya untuk meneliti lanjutan terhadap karakteristik psikologi pada setiap cabang olahraga.